Analisis Pengaruh Perilaku Konsumen Dalam Pengambilan Keputusan Pembelian Online Masyarakat Kota Mataram Pada E-Commerce Tiktok - Ulfiyani Asdiansyuri (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the influence of consumer behavior on the online purchase decisions of the people of Mataram City on the TikTok Shop platform. The approach used is quantitative with the survey method. Data was collected through a questionnaire distributed to 120 respondents who were active users of TikTok Shop. The data analysis technique uses multiple linear regression to test the influence of cultural, social, personal, and psychological factors on purchasing decisions. The results show that all consumer behavior variables have a positive and significant effect on online purchasing decisions. Psychological factors had the most dominant influence with a coefficient value of 0.41, followed by social factors of 0.32, personal factors of 0.21, and cultural factors of 0.18. A determination coefficient value (R²) of 0.68 indicates that 68% of the variation in purchasing decisions can be explained by these four variables, while the rest is influenced by other factors outside the research model.